Study of Medico-Legal Autopsies at Tehsil Level - Babur Rashid Chughtai, Muhammad Iqbal, Nadeem Afraz (Journal of Rawalpindi Medical College, 2013)
Background: To analyze the trend of homicidal deaths Methods: In this descriptive study autopies performed at THQ Hospital Taxila were analyzed. Every autopsy was started by identification of the dead body.External postmortem examination was started by examination of clothes.Inspection of the dead body was made from head to toe. Front, back and sides are examined with naked eye and magnifying lens. Temperature of the body and surrounding area was taken. All the natural orifices of body were scrutinized. Injuries, rigor mortis, postmortem lividity, stage of putrefaction and any other abnormality were noted down.The body was opened by straight incision starting from just above the thyroid cartilage to the pubic symphysis avoiding umbilicus. All the three cavities cranium, chest and abdomen were opened to see any injury, disease/abnormality. Results: Out of total 64 autopsies conducted, majority (87.5%) were males. Firearms remained the most common weapon. Nine (14.06%) persons died due to blunt injuries, 6.25% were murdered by sharp edged weapons and 4.69% died due to drowning. In 23.43% no cause of death could be detected. Adult age group (26-40 years) of persons remained most common victims. The skull and chest were the most targeted areas (17 each). Conclusion: Fire arm (51.56%) remains the most common weapon employed for homocide.